The phylogeny of marine and freshwater species of the genus Chloromyxum Mingazzini, 1890 (Myxosporea: Bivalvulida) based on small subunit ribosomal RNA gene sequences - Fiala, Ivan; Dyková, Iva (Folia parasitologica, 2004)
The small subunit ribosomal RNA gene (SSU rDNA) of two freshwater and one marine species of the genus Chloromyxum Mingazzini, 1890 were sequenced. The SSU rDNA trees obtained show the phylogenetic position of the marine species Chloromyxum leydigi Mingazzini, 1890 to be at the base of the freshwater clade, being well supported by a high bootstrap value. Chloromyxum cyprini Fujita, 1927 is closely related to Chloromyxum truttae Léger, 1906 and they represent a sister branch to raabeia sp., Myxidium sp. and Myxidium truttae Léger, 1930. Chloromyxum legeri Tourraine, 1931 is in a position ancestral to Myxidium lieberkuehni Bútschli, 1882 and Sphaerospora oncorhynchi Kent, Whitaker et Margolis, 1993. Three newly sequenced species of the genus Chloromyxum represent three separate lineages within the myxosporean tree and do not support the monophyly of this genus.
Keywords: sekvence nukleotidů; DNA primery; Phylogeny; Likelihood Functions; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; zvířata; Eukaryota; sladká voda; sekvenční analýza DNA; RNA ribozomální; Base Sequence; Fresh Water; Seawater; modely genetické; fylogeneze; RNA, Ribosomal; DNA Primers; pravděpodobnostní funkce; Models, Genetic; Animals; mořská voda